Public Perception of the Effects of Poverty on Economic Growth in Ghana - Omoniyi, Benjamin B.; Ogunwole, O. O.; Owolabi, S. O. (Advances in Social Sciences Research Journal, 2021)
The paper examined public perception of the effects of poverty on economic growth in Ghana. It specifically examined public perception on the relationship between poverty and economic growth in Ghana using a combination of descriptive statistics and Logit Model to analyse the primary data collected. The result revealed that poverty does not lower investment, per capita income was not high enough to reflect Ghana’s resources, it was also discovered that poverty programmes are effective and standard of living were inadequate. The paper further discovered that unemployment rate was not too high in Ghana. Corruption does not pose any threat to poverty and economic growth. There existed low income inequality between the rich and the poor but income was not evenly distributed while inflation does not increased the plight of the poor or deteriorates the living standard of the poor. The result further discovered that government performance was inadequate, lifespan was low, Ghana was able to meet MDGs goal by the end of 2015 but may not be able to sustain the achievement beyond 2015. Above all, poverty decisively slowed down the pace of economic growth in Ghana. The result of the Logit model showed that unemployment, corruption, secondary school enrollment, government policy, life-expectancy and poverty retarded economic growth while investment, aggregate consumption expenditure, pattern of income distribution and inflation, enhanced economic growth in Ghana. The result further revealed that only investment, aggregate consumption expenditure and inflation are the determinants of economic growth in Ghana. The paper concluded that poverty slowed down the pace of economic growth in Ghana. The paper therefore recommends that government should introduce and maintain policies that will permit improved relationships between poverty and other variables except investment, welfare and inflation so that they can positively and significantly contribute to increase economic growth in Ghana.